Visual Literacy: A Bet to Be Earned, ASAP (European Journal of Teaching and Education, 2020)
New language produces new thought. creativity, critical thinking, educational achievement, empathy towards others, and ability to decipher technology. The gap between looking and seeing can be bridged with observing– the process of building a catalogue of visual elements, a very important argument in front of the so called “narrowness of the education system.”The science of perception and the history of image through the ideas of Eratosthenes, Copernicus, Descartes, Aristotle, Confucius and many others, is to create meaning. Language is, and always will be, the ultimate form of communication.A book of illustrations and not with illustrations, could make complex arguments through that medium that he couldn’t with words alone. Words have been considered for many centuries of the human history, the superior currency of intellect. So, educators don’t know where to start when it comes to teaching visual literacy.Photos without captions can make us look only at the photo, and make judgments and inferences by ourselves. Teaching graphic design alongside poetry, could show that design it’s more than just lines and illustration. It a sophisticated way to grasp the procedure from an idea to a picture.The sooner teachers can really abandon the Learning Styles Theory and not label students as “visual learners”, since we all learn visually, the sooner students will be empowered to become visually literate.Not all serious ideas require words, and many are better off without them. Visual communication deserves its place, and can also serve education.